Labour Power = Average Cost of Production: Dissecting and Challenging the Tenets of Neoclassical Economics - Mr. Muhammad Qamar (Al-Qanṭara, 2023)
This paper provides an extensive examination of the pivotal Marxist economic principle, "Labour Power = Average Cost of Production," underscoring its crucial role in demystifying labor valuation within capitalist frameworks. The research delves into the commodification of labor power, conceptualized as workers' capacity to perform labor, contrasting it against the average cost of production, which encompasses the expenses necessary to sustain the workforce. Central to the discourse is the exploration of surplus value — the difference between workers' output and the wages they receive, representing profits pocketed by capitalists. The paper employs rigorous mathematical models and economic theories to illustrate this disparity, reinforcing the concept that workers' compensation often aligns merely with their subsistence costs, rather than the true value they add to the economy. Moreover, the analysis navigates contemporary economic landscapes, integrating modern variables and market dynamics into classical theories. It acknowledges potential deviations influenced by current market conditions, such as labor union interventions and regulatory policies, but reaffirms the fundamental tenet: the intrinsic linkage between labor valuation and production costs. By bridging classical Marxist theories with present-day economic realities, the study presents a nuanced perspective, validating the enduring applicability of the "Labour Power = Average Cost of Production" equation. It concludes by emphasizing the principle's significant implications for ongoing economic debates, labor rights discourses, and critiques of capitalist systems, asserting its necessity for informed socio-economic analyses in modern times.